THE ESSENCE OF SEMIOTICS AS A MEDIATOR OF COMMUNICATION AND COGNITION - Ismail Erton (Informascope, 2018)
Studies in modern linguistic theory to determine the scope and vision of human communication have shifted their attention to semiotics, in which actions speak louder than words as some say. The semiotic capacity of an individual reflects the effective and efficient usage of pragmatic competence in which the language user has the awareness of sociocultural and anthropological conventions processed and produced in the course of communication. Such a capacity also enables a systematic usage of cognitive skills, thereby developing the value of the communicative context and the perception of the individuals in various discourses. This paper attempts to identify, decode, and proceed utterances in a systematic mixture of psychological, physiological, sociological and anthropological procedures, in which non-verbal expressions appear as signs and symbols to communicate information. It is also argued that not only do individuals attain semiotic information naturally, they also do so  with proper semiotic training and research. In this respect, studies in biosemiotics explore the micro and the macro cosmos of human nature which are in a continuous cycle of interaction to process language. It is  further  established that the curiosity to discover the value systems in human communication through semiotic decoding means more than the mere study of language and its linguistic properties. Keywords: Pragmatics, Competence, Semiotics, Cognitive Theory, Communication, Cognition, Biosemiotics